Effect of Mishandling and Vending of Used Engine Oil on the Environment, Health and Urban Planning in Kaduna Metropolis: A Call to Action for a Paradigm Shift - Shehu, Patrick; Azi, Bulus; Dyachia Zakka, Solomon; Tanimu, Alheri; Akanbi-Lawal, Nuhu; Yakubu, Ayaka (Urban Planning and Construction, 2024)
This study examined the effect of mishandling and vending of used engine oil (UEO) on the environment, health, and urban planning. An evaluation of UEO handling, environmental and public health effects, spatial distribution of UEO vendors and contributing factors to choice of location, and the relationship between the vending location and the contributing factors to the choice of the location was provided. The research adopted multiple approaches including questionnaire administration, interview, observation, and application of a Global Positioning System, Geographic Information System, measuring tape, and a camera. An accidental/snowball sampling technique was viable for the study. Data collected were processed using Microsoft Excel. Descriptive and inferential statistical techniques were used. Results revealed the UEO was acquired from mechanic garages (41%) and stored in plastic containers (74%) until it was completely disposed of (91%). 52% had a hazy knowledge of the environmental effect of UEO, yet 45% rated the extent of its contamination as high. 59% were aware of its potential hazard which can get into the human body through ingestion but did not know it could get into the human body through contact with skin (74%) or breathing (61%). However, 84% wash their hands before a meal, with soap/water (67%), and change clothes after handling the used engine oil (69%). Most of the spots were located within 0-20 meters from the road (11), along the highways, occupying the metalled portion of the road, the road shoulders, setbacks, and walkways, blocking drainages and affecting the visual and aesthetic value of the environment. A larger proportion (40) revealed that visibility/accessibility guided their choice of location. Also, a low correlation coefficient of 0.32 was recorded. The study recommended the promotion of awareness programs, enforcement of environmental regulations, good hygiene practices, enforcement of standards and development regulations, and application of smart technology and big data.